Marketingový mix podniku - Vu, Anh duong (Vysoké učení technické v Brně. Fakulta podnikatelská, 2025)
Tato bakalářská práce se zabývá marketingovým mixem rodinné restaurace TOBU. Hlavním cílem je navhrnout změny vedoucí ke zlepšení marketingového mixu podniku za účelem rozšíření povědomí bez nutnosti rozsáhlých investic. Teoretická část se zabývá základními pojmy v marketingu. Druhá část představuje analýzu současného stavu podniku a konkurence na základě dostupných informací a dotazníkového šetření. V poslední části jsou představeny vlastní návrhy a doporučení pro zlepšení marketingového mixu podniku. Doporučení jsou vypracovány na základě výsledků vypracovaných analýz.

This bachelor’s thesis focuses on the marketing mix of the family-owned restaurant TOBU. The main objective is to propose changes that will improve the company’s marketing mix in order to increase brand awareness without the need for extensive investments. The theoretical part deals with basic marketing concepts. The second part presents an analysis of the current state of the business and its competitors, based on available information and a questionnaire survey. The final part contains original proposals and recommendations for improving the company’s marketing mix. These recommendations are based on the results of the conducted analyses.
Marketing Mix of the Company
Keywords: Marketing; marketingový mix; restaurace; marketingová komunikace; 7P; PESTLE; SWOT; Marketing; marketing mix; restaurant; marketing communication; 7P; PESTLE; SWOT